Colonoscopic titanium clipping to address appendiceal stump leakage: a case report - Liu, Jianjun; Yuan, Huayan; Xu, Xiulian; Yin, Longkuan; Wang, Wei; Fan, Wenhai; Bai, Xiangyu; Wang, Pan (Frontiers in Surgery, 2023)
The incidence of appendiceal stump leakage (ASL) is extremely low and heterogeneous, which has been reported to be approximately 0.5-1.0%. It is a catastrophic complication with high mortality rate despite its low morbidity. Once it occurs, it will put the doctor in a passive position because dealing with the leakage is much more cumbersome than appendectomy. We extensively reviewed the literatures on ASL, focusing on the management and prognosis. Unsurprisingly, all of the physicians advocated extended resection, which apparently gave them sufficient confidence. However, partial cecum resection, cecostomy or terminal ileectomy, any of which is extremely invasive and destructive. So, the patients had to experience great mental and physical trauma, longer hospital stays, higher rates of wound infection, more costs and even a third surgery. Therefore, are there any better approaches for ASL? In this article, we report a case of ASL who successfully underwent endoscopic treatment. A 70-year-old male was admitted with gangrenous perforated appendicitis with a large ilio-psoas abscess. Appendectomy, ilio-psoas abscess debridement and sufficient drainage, appendicular stump repairment and closure, and terminal ileostomy were performed respectively. Three months later, the patient was readmitted and the stoma reversal was performed as scheduled. 7 days later, ASL was found when a liquid diet was applied routinely due to right lower quadrant pain and low fever. Finally, with the periappendiceal abscess was completely drained, we clamped the appendiceal orifice with 5 titanium clips under an electronic colonoscope, which eventually sealed the leakage and avoided extended resection.